2004
DOI: 10.1161/01.atv.0000124103.86943.1e
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Perfusion and Network Remodeling in a Microvascular Construct After Implantation

Abstract: Objective-We have previously demonstrated the ability to construct 3-dimensional microvascular beds in vitro via angiogenesis from isolated, intact, microvessel fragments that retain endothelial cells and perivascular cells. Our objective was to develop and characterize an experimental model of tissue vascularization, based on the implantation of this microvascular construct, which recapitulated angiogenesis, vessel differentiation, and network maturation. Methods and Results-On implantation in a severe combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 142 publications
(143 citation statements)
references
References 26 publications
3
140
0
Order By: Relevance
“…The ability to precisely control in vitro experimental conditions directly led to identifying the mechanisms of many fundamental aspects of this process over the past several decades (5)(6)(7)(10)(11)(12)(13)(14). Several groups have recently shown that microvascular structures that are preformed in vitro by using endothelial and smooth muscle progenitor cells can anastomose with the host vasculature when implanted in a nude mouse model (15)(16)(17)(18)(19)(20). In this study we demonstrate that human mesenchymal stem cells (hMSCs) coimplanted with endothelial cells (ECs) in a fibronectin-containing collagen gel act as a source of perivascular cells and generate a stable functional vasculature within a porous scaffold.…”
mentioning
confidence: 99%
“…The ability to precisely control in vitro experimental conditions directly led to identifying the mechanisms of many fundamental aspects of this process over the past several decades (5)(6)(7)(10)(11)(12)(13)(14). Several groups have recently shown that microvascular structures that are preformed in vitro by using endothelial and smooth muscle progenitor cells can anastomose with the host vasculature when implanted in a nude mouse model (15)(16)(17)(18)(19)(20). In this study we demonstrate that human mesenchymal stem cells (hMSCs) coimplanted with endothelial cells (ECs) in a fibronectin-containing collagen gel act as a source of perivascular cells and generate a stable functional vasculature within a porous scaffold.…”
mentioning
confidence: 99%
“…3). The resulting microvessel networks, characterized previously (16,33), have a collagen IV basement membrane, stain for von Willebrand factor, and integrate with host vessels after in vivo implantation (33).…”
Section: Resultsmentioning
confidence: 96%
“…18 A recent report describes the use of the rat omentum to prevascularize a cardiac patch, although no mention was made of immune suppression, and there was no tracking of the transplanted cells. 19 There are also several reports of EC transplantation in immune-compromised animals [20][21][22] (see below). Here we report that native, unmodified EC develop over 21-60 days into mature blood vessels in an allogeneic transplant model.…”
Section: Discussionmentioning
confidence: 99%